Design and Implementation of Low-Cost PMU for Off-Nominal Frequency and DDC in Compliance with IEEE C37.118 Standard - Rana, Ankur Singh; Jnaneswar, Kolli; Gadhiraju, Mouna Krishna; Kumar, Neeraj; Wani, Shufali Ashraf; Thomas, Mini Shaji (Distributed Generation & Alternative Energy Journal, 2023)
The transition of the conventional power grid into the smart grid requires continuous monitoring of integrated grids speared over wide-area through Phasor Measurement Units (PMU). These PMUs additionally perform protection and state estimation functions in the smart grid. This paper discusses implementation of a new phasor estimation method to eliminate the effects of Decaying DC (DDC) component and off-nominal frequencies during the extraction of the phasors from a relaying signal. The practical implementation of the proposed method in a low-cost microcontroller (ESP32-WROOM-32 development board) in compliance with the requirements of IEEE C37.118.1a-2011 standard is also demonstrated. The analysis of various existing algorithms estimating the phasors is carried out. The microcontroller is programmed with the best among the analysed algorithm and its feasibility to function as a proper Phasor Measurement Unit is tested. The newly designed PMU is rigorously tested with different estimation methods compliant with IEEE C37.118a-2011 standard. The comparison of the proposed method with different phasor estimation algorithms is also discussed.